ANTIDIABETIC ACTIVITY FROM ETHANOL EXTRACT OF KLUWIH’S LEAF (Artocarpus camansi) - Marianne Marianne; Yuandani Yuandani; Rosnani Rosnani (Jurnal Natural, 2011)
Research on antidiabetic activity of ethanol leaf extracts Kluwih (Artocarpus camansi) has been carried out to determine the antidiabetic activity of ethanol extract of leaves kluwih (EELK) of mice using glucose tolerance test. The study began by dividing the mice into 6 groups. Group 1 was given 1% CMC, group 2 to group 4, given EELK 50, 100, 200, 400 mg / kg bw, respectively, and group 6  administered with glibenclamide 0.45 mg/kg bw. Thirty minutes later each group was given glucose 30 mg/kg bw. After 30 min of glucose loading, blood glucose levels of mice were measured, and measured again at minute 60, 90, 120 and 150 minutes. The results showed that the glucose tolerance test EELK a significant effect in lowering blood glucose levels compared to controls at 30 and 60 minutes after administration of glucose. At minute 90 to 150, the effect of blood glucose levels EELK restore back to normal. EELK demonstrated ability to reduce blood glucose levels, and EELK doses of 50 and 100 mg/kg bw showed antidiabetic effects better than a dose of 200 and 400 mg/kg bw. Increasing doses showed antagonistic effects: the ability to increase blood glucose levels.